Um aplicativo com reconhecimento de toques e gestos para concepção de ambientes virtuais em dispositivos móveis - Braga, Pedro Henrique Cacique (2012)
The educational scenario has been constantly changed by the emergence of new technologies. Several researches and tools are developed in order to reframe the ways of learning and teaching inside and outside school. Information and communication technologies have caused a deep revolution in people\'s way of life in the past decades. One of the ranges that couldn\'t avoid to be affected is education and enablement (Kubota, DEMOLINER e FIGUEIREDO, 2011). The education has gotten new perspectives with the learning based on interactive technologies. Learning becomes a dynamic process and no more dependent on geographical boundaries. Hence, learning techniques arise, supported by mobile computing, which is able to take new information to the user at any time anywhere (mobile-learning or simply m-learning). This work approaches current usage of m-learning and presents a strategy of development in educational applications, using mobile devices associated with Virtual Environments and Augmented Reality. With that purpose, pattern recognition techniques related to gesture and touch are adapted and strategies of those patterns associations with library elements and between themselves, aiming to conceive virtual and augmented environments as a support for teaching. As a proof of concept, the application was implemented and evaluated, grounded in such techniques, allowing the conception of Physics experiments (Classic Mechanics).